+0  
 
0
252
3
avatar

Solve:

 

y=-3x-6

 

3x-y=8

Guest Apr 17, 2017
 #1
avatar
0

Plug in -3x-6 for y. Simplifying you should get  6x-6=8 solving that gives you 14/6 or 7/3 for x. Plug that back in for x in the first equation and 2.3333333333333333*3-6 = 0.9999999999999999 or 1 rounded :). Hope this helps 

Guest Apr 17, 2017
 #2
avatar
0

Thank you! :D

Guest Apr 17, 2017
 #3
avatar+7002 
0

\(y = -3x - 6\\ -y = 3x + 6\\ 3x - y = 8\\ 3x + (3x + 6) = 8\\ 6x + 6 = 8\\ x +1 = \dfrac{4}{3}\\ x = \dfrac{1}{3}\\ y = -3(\dfrac{1}{3})-6 = -7\\ \therefore x = \dfrac{1}{3};y=-7\)

MaxWong  Apr 18, 2017

16 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.